(3GdeMGSHI GdeGdjI MSH GdfXGe GdeMGSHj GdeGdj (BSCF /s - (3UdGM, MhGS s ((3GdLRGFQ(B: s (3OGQ CLjGd GdQbej (B, s, 2024)
(3jVe GdcJGH CSS heHGOF GdeMGSHI GdeGdjI, GdeHGOF hGdaQVjGJ hGdNUGFU GdeMGSjHI , GdCSS hGdNUGFU GdeMGSHjI,eTQhY JegjOj ddfXGe GdeGdj GdeMGSHj GdLOjO(B(SCF) (3GdJOabGJ hGdejRGfjI GdeMGSHjI, GdOaGJQ GdeMGSHjI hGdOhQI GdeMGSHjI, OaJQ GdjhejI, ejRGf GdeQGLYI, OQGSI GdMSGHGJ GdeOhfI hjVe GdJKHjJGJ hGdJNajVGJ, GdahJQI hMSGHGJ GdZjQ, GdZdGaGJ, GdGgJdGcGJ hNSGQI GdbjeI haj GdCNjQ feGPL ddGeJMGfGJ GdSOGSj GdKGfj (B.s
Keywords: (3GdeGdjI GdYGeI(B- (3eMGSHIs; (3GdeMGSHIs